Pogostost uporabe informacijsko-komunikacijske tehnologije pri pouku geografije v Sloveniji - Jesenek Bračko, Petra; Kolnik, Karmen (Revija za elementarno izobraževanje, 2013)
Frequency of Using ICT in Teaching Geography in Slovenia. This article presents an analysis of expert sources and gives an overview of the integration of ICT in teaching geography in Slovenia. It presents the main results of different studies, which show representative usage of ICT in geography lessons. The studies included herein were carried out by individuals as well as by state educational institutions. The article highlights, among other things, some major projects since 1994, which have had a significant influence on the introduction of technology in the educational process and on teachers’ and students’ digital literacy. The core of the article presents the results of a 2010 survey on equipment of geography classrooms and the use of ICT in geography lessons in Slovenian schools. We looked into the opinions of geography teachers about the frequency of using information and communication technologies in geography lessons in Slovenia. The respondents also discussed the possible reasons for rare usage of ICT and their qualification for actively using ICT in teaching.
Keywords: information and communication technology; geography; teacher; equipment; usage